The effect of internal through coolant on grinding performance on AISI1020 mildsteel - Rahim, E.A.; Mohid, Z.; Rahman, A.H.A.; Bahman, M.F. (Trans Tech Publications, 2012)
This paper presents the experimental result of grinding performance with an internal through coolant supply. Using this method, the coolant is delivered through the grinding wheel and this concept will allowed the coolant supplied directly to the contact zone. The experiment has been conducted on thin plate of AISI1020 mild steel, to ensure the effectiveness when using internal through coolant supply and the grinding result using internal through. The result of internal through coolant supply was compared with an external coolant supply. It was revealed that the temperature was lower and surface roughness was smaller when the proposed coolant supply concept used.